马来西亚华语口语中“一下”特殊结构研究 = Yixia constructions in Malaysia spoken Mandarin - 蔡可涵 Chua, Ke Han (2018)
“一下”是现代汉语中表达“小量”意义的重要数量短语，目前现代汉语有关该结构的研究多不胜数，但对马来西亚华语“一下”特殊结构的研究成果甚少。除了一般数量短语的用法及表达“小量”的语法意义外，“一下”在马来西亚华语中还具有其他独特的用法。本文的目的是进一步调查马来西亚华语中“一下”特殊结构的使用情况。 本研究通过问卷调查的形式，考察马来西亚华人受试者对“V一下”、“VV”、“VV下”、“VV一下”和“V下V下”五种构式的接受程度，并以调查结果的数据为基础进行分析，讨论这五种构式的语法意义、语用功能及对动词的选择限制。 本研究调查结果发现，上述五种构式个别具有表达“时量短、动量小”、表达尝试义、表达礼貌客气、表示动作持续进行及表示单次实现动作的功能，且普遍上被马来西亚华人所接受。在动词选用方面，非自主及非持续性动词、单音节及双音节动词皆能以“V一下”、“VV下”及“VV一下”的形式出现在马来西亚华语口语中。本文推断其中“VV下”和“VV一下”特殊构式是受到广东话和福建话影响而形成的。 In Modern Mandarin Chinese, yixia is one of the most important numeral classifier structures expressing the delimitative aspect (i.e. “small in quantity”). In Malaysia Mandarin, however, yixia can occur in a wider type of constructions with richer functions than its counterpart in Mainland China Mandarin. This study aims to provide a comprehensive investigation of the constructions and functions that yixia is associated with in Malaysia Mandarin. Specifically, this study conducts a questionnaire survey of five “synonymous” constructions (V yixia, VV, VV xia, VV yixia, V xia V xia) for collection of the acceptability judgement by native speakers of Malaysia Mandarin. This study finds that (1) all five constructions are highly acceptable among native speakers of Malaysia Mandarin; (2) the five constructions can function as a marker of (a) delimitative aspect (i.e. do something a little bit or a little while), (b) tentative aspect, (c) politeness, (d) continuous aspect, and (e) actions that are semelfactive; (3) the five constructions allow a wider range of verb types, including verbs that are not spontaneous or durative, as well as verbs that are monosyllabic or disyllabic. This study proposes that of the five constructions, VV xia and VV yixia in Malaysia Mandarin are the products of language contact to Cantonese and Hokkien.